Schizophrenia - Insight, Depression: A correlation study - Ananda Reddy Endreddy; Subahani shaik; Bhagawan Rajana (International Journal of Medical Research and Review, 2016)
Background: Schizophrenia is one of the severe forms of mental illness which demands enormous personal and economical costs. Recent years have attracted considerable interest in the dual problem of depression in schizophrenia and its relation to insight. Most clinicians believe that poor insight in patients with schizophrenia, though problematic for treatment adherence, may be protective with respect to suicide.Aims and objectives: Our study was aimed to find out the correlation between insight and depression in schizophrenic population.Materials and Methods: Present study was a cross sectional, single centred, correlation study done in total of 60 subjects. Subjects aged between 20 to 60years, diagnosed to have schizophrenia as per ICD-10 and who have given written consent been considered for the study. Subjects who had other psychiatric disorders such as mood disorder, schizoaffective disorder, mental retardation, epilepsy or detectable organic disease and co morbid substance abuse were excluded from the study. Schizophrenics with acute exacerbation were also excluded from the study. For insight assessment, schedule for assessment of insight (SAI), a three item rating scale was used. For the assessment of depressive symptoms, a nine item rating scale, Calgary Depression Rating Scale (CDRS) was administrated.Results: Insight and depression were strongly correlated in schizophrenic population with a Pearson correlation coefficient of 0.758. The correlation between insight and depression was high in subjects with less duration of illness.Conclusions: Our study suggests that poor insight may protect against depression in the early stages of recovery from schizophrenia. The correlation between insight and depression was high in subjects with less duration of illness.